ISLAMIC POINT OF VIEW REGARDING PERMITTED AND PROHIBITED THINGS FOR MUSLIM (Singaporean Journal of Business Economics and Management, 2020)
It is fact that Islam has provided distinct features from the other religions of the world because it has given guidelines about the things those are strongly encouraged and those are strongly discouraged. Actually these are termed as halal (Permitted) and halal (Prohibited). And Muslims must follow all these guidelines so that they could succeed in this world and the world hereafter. Similarly, halal things are permitted for trade and business dealings while haram things are prohibited in business dealings. But unfortunately, in Muslim countries, both types of business are being held. Therefore, no one could imagine from seeing their business whether this is Muslim or non-Muslim country. This is sorrowful thing for Muslim countries and its inhabitants that are neglecting some of commandments of God. The problems about permitted and prohibited things do not confine in edible items but it also covers the communication techniques and media also. In media, publicity and advertising ads are being done without considering ads, these are allowed or not in Islam. Actually, these types of ads that have naked model girls in ads which are not suitable in the Islamic culture and civilization and these also encourage non Islamic values. Govt. authorities should do such policies to control non Islamic values and prohibited things must be strictly banned through rules and regulations.